Effectiveness of Cymbopogon citratus L. Essential Oil to Inhibit the Growth of Some Filamentous Fungi and Yeasts - Irkin, Reyhan; Korukluoglu, Mihriban (Journal of medicinal food, 2009)
Lemon grass (Cymbopogon citratus L.) oil has been known as having therapeutic and antibacterial properties, and its antifungal activity is currently the subject of renewed interest. This study aimed to verify the effectivenesses of C. citratus essential oil to inhibit the growth/survival of some fungi (Alternaria alternata, Aspergillus niger, Fusarium oxysporum, and Penicillium roquefortii) and yeasts (Candida albicans, Candida oleophila, Hansenula anomala, Saccharomyces cerevisiae, Schizosaccharomyces pombe, Saccharomyces uvarum, and Metschnikowia fructicola). C. citratus essential oil showed effectiveness in inhibiting the growth of all fungi by disc diffusion and broth dilution bioassay. Minimum inhibitory and minimum fungicidal concentrations between 0.062 and 20 microL/mL were determined. The Clinical and Laboratory Standards Institute agar-based method was also applied for A. niger and C. albicans. Data show the strong antifungal properties of lemon grass oil (C. citratus) in vitro.